Current diagnosis & treatment : neurology - Brust, John C. M. (John Calvin M.), 1936- (New York : McGraw-Hill Medical, 2019)
This clinically oriented resource will be valuable to anyone who sees patients with neurologic complaints, whether in primary care or the neurology clinic. The Third Edition provides a complete update of all chapters, with special emphasis on conditions for which new drugs are available (such as headache, pain, neuropathy, and sleep disorders), as well as the most rapidly advancing conditions in the field such as epilepsy, multiple sclerosis, and stroke
I. Neurologic investigations: 1. Electroencephalography / Tina Shih -- 2. Electromyography, nerve conduction studies, & evoked potentials / Dora Leung -- 3. Neuroradiology / John P. Loh -- II. Neurologic disorders: 4. Coma / John C.M. Brust -- 5. Aphasia, apraxia, & agnosia / John C.M. Brust -- 6. Hearing loss & dizziness / Jack J. Wazen, Soha N. Ghossaini, & Benjamin Wycherly -- 7. Epilepsy & seizures / Tina Shih -- 8. Headache & facial pain / Mark W. Green -- 9. Dementia & memory loss / Karen Marder [and others] -- 10. Cerebrovascular disease : ischemic stroke / Brian-Fred M. Fitzsimmons & Marc Lazzaro -- 11. Cerebrovascular disease : hemorrhagic stroke / Richard A. Bernstein -- 12. Central nervous system neoplasms / Christopher E. Mandigo & Jeffrey N. Bruce -- 13. Paraneoplastic neurologic syndromes / Lakshmi Nayak, Alfredo D. Voloschin & Andrew B. Lassman -- 14. Trauma / Katja E. Wartenberg & Stephan A. Mayer -- 15. Movement disorders / Amanda Deligtisch, Blair Ford, Howard Geyer, & Susan B. Bressman -- 16. Ataxia & cerebellar disease / Claire Henchcliffe -- 17. Multiple sclerosis & demyelinating diseases / Bruce A.C. Cree -- 18. Nontraumatic disorders of the spinal cord / Olajide Williams & Michelle Sterne -- 19. Peripheral neuropathies / Clifton Gooch & Tanya Fatimi -- 20. Motor neuron disease / Michio Hiarano -- 21. Autonomic disorders / Louis H. Weimer -- 22. Myasthenia gravis & other disorders of neuromuscular junction / Shanna Kathlyn Patterson, Petra Kaufmann, & Marisa Schiller Sosinsky -- 23. Diseases of muscle / Olajide Williams -- 24. Mitochondrial diseases / Michio Hirano -- 25. Neurologic intensive care / Santiago Ortega-Gutierrez & Alan Z. Segal -- 26. Bacterial, fungal, & parasitic infections of the nervous system / Barbara S. Koppel & Todd Hayano -- 27. Viral infections of the nervous system / Jeffrey Sevigny, Jennifer Frontera, & James M. Noble -- 28. HIV neurology / Ned Sacktor [and others] -- 29. Prion diseases / Lawrence S. Honig -- 30. Disorders of cerebrospinal fluid dynamics / John C.M. Brust -- 31. Sleep disorders / Anne Helena Remmes -- 32. Systemic & metabolic disorders / Cheryl A. Jay -- 33. Alcoholism / John C.M. Brust -- 34. Drug dependence / John C.M. Brust -- 35. Psychiatric disorders / Eric R. Marcus -- 36. Neurological disorders of childhood & adolescence.
BIBINDX
Keywords: Nervous System Diseases -- diagnosis; Nervous System Diseases -- therapy